Crossed cerebellar diaschisis in acute ischemic stroke: Impact on morphologic and functional outcome. Issue 11 (November 2017) - Kunz, Wolfgang G; Sommer, Wieland H; Höhne, Christopher; Fabritius, Matthias P; Schuler, Felix; Dorn, Franziska; Othman, Ahmed E; Meinel, Felix G; von Baumgarten, Louisa; Reiser, Maximilian F; Ertl-Wagner, Birgit; Thierfelder, Kolja M
Crossed cerebellar diaschisis (CCD) is the phenomenon of hypoperfusion and hypometabolism of the contralateral cerebellar hemisphere caused by dysfunction of the related supratentorial region. Our aim was to analyze its influence on morphologic and functional outcome in acute ischemic stroke. Subjects with stroke caused by a large vessel occlusion of the anterior circulation were selected from an initial cohort of 1644 consecutive patients who underwent multiparametric CT including whole-brain CT perfusion. Two experienced readers evaluated the posterior fossa in terms of CCD absence (CCD−) or presence (CCD+). A total of 156 patients formed the study cohort with 102 patients (65.4%) categorized as CCD− and 54 (34.6%) as CCD+. In linear and logistic regression analyses, no significant association between CCD and final infarction volume (β = −0.440, p  = 0.972), discharge mRS ≤ 2 (OR = 1.897, p  = 0.320), or 90-day mRS ≤ 2 (OR = 0.531, p  = 0.492) was detected. CCD+ patients had larger supratentorial cerebral blood flow deficits (median: 164 ml vs. 115 ml; p  = 0.001) compared to CCD−patients. Regarding complications, CCD was associated with a higher rate of parenchymal hematomas (OR = 4.793, p  = 0.035). In conclusion, CCD is frequently encountered in acute ischemic stroke caused by large vessel occlusion of the anterior circulation. CCD was associated with the occurrence of parenchymal hematoma in the ipsilateral cerebral infarction but did not prove to significantly influence patient outcome.